Role of CD133/NRF2 Axis in the Development of Colon Cancer Stem Cell-Like Properties - Park, Jimin; Kim, Seung Ki; Hallis, Steffanus Pranoto; Choi, Bo-Hyun; Kwak, Mi-Kyoung (Frontiers in Oncology, 2022)
Cancer stem cells (CSCs) exhibit insic therapy/stress resistance, which often cause cancer recurrence after therapy. In this study, we investigated the potential relationship between the cluster of differentiation (CD)-133, a CSC marker of colon cancer, and nuclear factor erythroid 2-like 2 (NFE2L2; NRF2), a master transcription factor for the regulation of multiple antioxidant genes. In the first model of CSC, a sphere culture of the colorectal cell line HCT116, showed increased levels of CD133 and NRF2. Silencing of CD133 reduced the levels of CSC markers, such as Kruppel-like factor 4 (KLF4) and ATP-binding cassette subfamily G member 2 (ABCG2), and further suppressed the expression levels of NRF2 and its target genes. As a potential molecular link, CD133-mediated activation of phosphoinositide 3-kinase/serine-threonine kinase (PI3K/AKT) signaling appears to increase the NRF2 protein levels via phosphorylation and the consequent inhibition of glycogen synthase kinase (GSK)-3β. Additionally, NRF2-silenced HCT116 cells showed attenuated sphere formation capacity and reduced CSC markers expression, indicating the critical role of the NRF2 pathway in the development of CSC-like properties. As a second model of CSC, the CD133high cell population was isolated from HCT116 cells. CSC-like properties, including sphere formation, motility, migration, colony formation, and anticancer resistance, were enhanced in the CD133high population compared to CD133low HCT116 cells. Levels of NRF2, which were elevated in CD133high HCT116, were suppressed by CD133-silencing. In line with these, the analysis of The Cancer Genome Atlas (TCGA) database showed that high levels of CD133 expression are correlated with increased NRF2 signaling, and alterations in CD133 gene or expression are associated with unfavorable clinical outcome in colorectal carcinoma patients. These results indicate that the CD133/NRF2 axis contributes to the development of CSC-like properties in colon cancer cells, and that PI3K/AKT signaling activation is involved in CD133-mediated NRF2 activation.